Therapy with Cogitum in children with speech disorders - M. Yu. Bobylova (Русский журнал детской неврологии, 2022)
Developmental dysphasia is a speech disorder with normal hearing and intelligence, which develops against the background of organic brain damage in the period up to 3 years of life. In addition to speech disorders in dysphasia, motor and coordinator, sensory (disturbances in sensitivity and perception), and psychopathological manifestations can be noted. Diagnosis of speech disorders is very difficult, requires the exclusion of hearing loss and mental illness. After a successful diagnosis, speech therapy correction, behavioral therapy and developmental sessions with a psychologist are necessary. In some cases, neurotrophic drugs are prescribed. This article analyzes our own data on the use of the drug “Cogitum” in 140 children in comparison with the control group (n = 40), who had the same classes as in the main group, but without the use of Cogitum. Improvement in group 1 was shown.